Sex-specific association between elective cesarean section and growth trajectories in preschool children: A prospective birth cohort study - Zhang, Shanshan; Zhou, Jixing; Yang, Mengting; Zhang, Fu; Tao, Xingyong; Tao, Fangbiao; Huang, Kun (Frontiers in Public Health, 2022)
Background Elective cesarean section (ECS) primarily contributes to the rising cesarean section (CS) rate, and much attention has been attracted to its health consequences. The association between ECS and overweight and obesity in children has been controversial, and few studies distinguished ECS with medical indications from those without indications. Based on a large sample birth cohort, we aim to examine the association of ECS with or without medical indications on children's physical development by using repeated anthropometric data from birth to 6 years of age. Methods A total of 2304 mother-child pairs with complete data on delivery mode and children's anthropometric measurements were recruited from the Ma'anshan-Anhui Birth Cohort (MABC) in China. ECS was the main exposure in this study, and the primary outcomes were children's growth trajectories and early adiposity rebound (AR). Children's BMI trajectories were fitted by using group-based trajectory models and fractional polynomial mixed-effects models. The association between ECS and children's growth trajectories and early AR was performed using multiple logistic regression models. Results Among 2,304 mother-child pairs (1199 boys and 1105 girls), 1088 (47.2%) children were born by CS, including 61 (5.6%) emergency CS, 441 (40.5%) ECS with medical indications, and 586 (53.9%) ECS without medical indications. After adjusting for potential confounders, it was found that ECS with medical indications was associated with a “high level” of BMI trajectory (OR = 1.776; 95% CI: 1.010–3.123), and ECS without medical indications was associated with early AR (OR = 1.517; 95% CI: 1.123–2.050) in girls. In boys, we found that ECS without medical indications was unlikely to experience an accelerated growth trajectory (OR = 0.484; 95%CI: 0.244–0.959). Conclusions ECS may be related to girls' “high level” BMI trajectories and early AR. If causal, the findings will provide an evidence-based reference for early life interventions for childhood obesity.